Faktor-Faktor yang Mempengaruhi Penghindaran Pajak pada Perusahaan Manufaktur di Bursa Efek Indonesia - Wen Wen; Maulana Malik Muhammad (UNIVERSITAS KALBIS, 2022)
This study aims to obtain empirical evidence and analyze the factors that influence tax avoidance of the manufacturing companies in Indonesia Stock Exchange. The independent variables tested in this study were firm size, return on asset, sales growth, leverage,Capital Intensity, composition of the independent board, and audit comittee. While the dependent variable in this study is Cash effective tax rate (CETR). This study produced a sample of 159 manufacturing companies listed on the Stock Exchange in the period 2018 to 2020. The method of sampling used purposive sampling and this study used multiple linear regression analysis. This study provides results that were firm size, sales growth, leverage,Capital Intensity, composition of the independent board, and audit comittee have no influence to tax avoidance. While the return on asset have influence to tax avoidance.